Differential of Antioxidant Ability, CD4+T Cells Count and Viral Load in HIV Infected Patients on cART in Yaounde, Cameroon - Georges Teto; Jules S. Kenmegne; Joseph Fokam; Flore N. Nguemaim; Beatrice Dambaya; Desire Takou; Reine C. Dombu; Nadege M. Goumkwa; Anatole C. Pieme; Alexis Ndjolo (Journal of Current Viruses and Treatment Methodologies, 2020)
Background Decreased antioxidant ability is one of the worsening conditions in AIDS.We aimed to evaluate total antioxidant ability among others, and their variation in HIV infected patients following their CD4+T cells count and viral load, in a context of new ART scarcity in most LMICs. Material and Methods We conducted a cross sectional study on 167 individuals (76 controls, 33 treatments naïve and 58 HIV-1 infected patients on ART). We assessed their plasma total antioxidant ability (FRAP), malondialdehyde (MDA) and thiol (SH) groups using standard spectrophotometric methods, then we calculated lipid peroxidation index (LPI). Statistical analysis was performed using GraphPad Prism 6. Data were analyzed by two-tailed unpaired t-test for two groups’ comparison and ANOVA for more than two groups. Pearson correlation between CD4+T cells count, viral load and the above markers was determined; P ≤ 0.05 was considered statistically significant. Results The following controls/naïve/treated subjects’ values for FRAP(mM) (1.907±0.074/1.77±0.05/1.695±0.03); MDA(μΜ) (0.781±0.081/1.115±0.118/ 1.342±0.109); SH (μΜ) (2.747±0.130/1.582±0.197/1.498 ±0.140)and LPI (0.43±0.61/ 0.61±0.7/2.59±0.83) were all obtained with P ≤ 0.05. The FRAP increased only with 3TC+TDF+EFV and 3TC+ABC+NVP cART while MDA decrease significantly with the later(p=0.027). MDA and LPI significantly increased in heavily treated patients with p<0.0014 and p=0.0001 respectively. overall, the patients showed an increase of viral loads following a decrease of CD4+T cells (r= -0.803, p=0.016) but 3TC+TDF+EFV seem to better manage the both. The only significant correlation was established between SH groups and CD4+Tcells count (r=0.447; p=0.0006); Conclusion Our study showed that thiol groups may be protective againstCD4+Tcells count depletion and that the cART 3TC+TDF+EFV, 3TC+ABC+NVP may be helpful in fighting against free radical generation and particularly 3TC+TDF+EFV as controlling CD4+Tcells count and viral load in long term treated patients. The study particularly showed the implication of cART in increasing lipid peroxidation index following the treatment duration in heavily treated patients, which aggravated their conditions in an area where drug options are limited, calling for new drugs availability and personalized medicine.
Keywords: Total antioxidant ability